Analisis implementasi gastrodiplomasi Thailand dalam mempererat hubungan dengan negara muslim dunia menggunakan halal food - Murdhania, Dafa (Nur Science Institute, 2022)
This study discusses the implementation of gastro-diplomacy carried out by the Thai government, which aims to strengthen relations with the world's Muslim countries using instruments in the form of halal food. This study aims to describe the policies implemented by the Thai government so that it can develop halal food in various Muslim countries. In addition, this study aims to determine the challenges faced by the Thai government in developing halal food, considering that Thailand has a Muslim minority population. Writing in this research uses a qualitative descriptive method with data collection techniques carried out through literature study techniques. The study results show that Thailand has succeeded in developing halal food by launching a program known as